VP95 Getting the Best Of 3 Ways-Merging EUnetHTA GRADE And Cochrane Guides. (2019) - Ballini, Luciana; Formoso, Giulio; Bassi, Maria Chiara; Bonvicini, Laura; Bottazzi, Paolo; Rossi, Paolo Giorgi; Venturelli, Francesco; Vicentini, Massimo
Abstract : Introduction: European cooperation in Health Technology Assessment (HTA) requires joint assessments to be of high quality, providing findings transferable into national HTA report. To this aim, we piloted the combining of methodological guidance of EUnetHTA for Relative Effectiveness Assessment (REA), GRADE for selection/rating of outcomes and assessing quality of evidence, and Cochrane for Systematic Reviews, while carrying out a collaborative REA on Femtosecond Laser Assisted versus Standard Cataract Surgery. Methods: While developing the collaborative REA, we used the three organizations' handbooks, templates and tools for Scope, Project Plan (PP), Summary of Findings, Effectiveness (EFF) and Safety (SAF) domains. We structured the PP according to the EUnetHTA template and added detailed methods on EFF and SAF systematic reviews, as per Cochrane Handbook. For the Scope we convened a multidisciplinary panel for selection and rating of importance of outcomes and clinically significant difference, using the GRADEpro platform. We developed the complete report adopting the EUnetHTA REA Core Model. We used Cochrane's tool Revman to assess risk of bias of included studies for each outcome, and to carry out metanalyses. We applied the GRADE approach to assess quality of evidence for each outcome and to express level of certainty in the estimates. We used the Cochrane handbook's guidance for structuring a scientific abstract and a Plain Language Summary to integrate the Summary of Findings. Results: The PP resulted in a detailed scientific and operational protocol, receiving extensive and constructive internal and external peer review. Reporting of EFF and SAF domains followed EUnetHTA Assessment Elements while keeping the order of stakeholders' rating of outcomes' importance. Graphic representation of risk of bias for each outcome contributed to immediacy of the data quality assessment and transparency of the judgement on certainty. The scientific abstract and the Plain Language Summary, facilitated the external dissemination of results. Conclusions: Merging of the three most important methodological contributions in the field proved successful without altering the distinctive trait of the REA.